2008
DOI: 10.1101/gad.1689908
|View full text |Cite
|
Sign up to set email alerts
|

Laminin-511 is an epithelial message promoting dermal papilla development and function during early hair morphogenesis

Abstract: Hair morphogenesis takes place through reciprocal epithelial and mesenchymal signaling; however, the mechanisms controlling signal exchange are poorly understood. Laminins are extracellular proteins that play critical roles in adhesion and signaling. Here we demonstrate the mechanism of how laminin-511 controls hair morphogenesis. Dermal papilla (DP) from laminin-511 mutants showed developmental defects by E16.5, including a failure to maintain expression of the key morphogen noggin. This maintenance was criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(105 citation statements)
references
References 66 publications
(66 reference statements)
2
102
0
Order By: Relevance
“…However, considering that DP growth suppression due to BIO (Yamauchi and Kurosaka, 2009) represents a major drawback of DPAC, BIO may be substituted by recombinant WNT3A (Kishimoto et al, 2000;Shimizu and Morgan, 2004) to maintain the intrinsic properties and proliferative capacity of dpacDP cells. Because past reports suggested that activation of multiple biological pathways is necessary to fully maintain DP characteristics in vitro (Kishimoto et al, 2000;Shimizu and Morgan, 2004;Rendl et al, 2008), DPAC could be more potentiated by the addition of activators of other signaling pathways, including the Sonic hedgehog, Notch, and Endothelin pathways (Gao et al, 2008;Driskell et al, 2009;Hu et al, 2010). In contrast to DP cells, fibroblasts cultured in DPAC reduced ALP expression (data not shown).…”
Section: Discussionmentioning
confidence: 86%
“…However, considering that DP growth suppression due to BIO (Yamauchi and Kurosaka, 2009) represents a major drawback of DPAC, BIO may be substituted by recombinant WNT3A (Kishimoto et al, 2000;Shimizu and Morgan, 2004) to maintain the intrinsic properties and proliferative capacity of dpacDP cells. Because past reports suggested that activation of multiple biological pathways is necessary to fully maintain DP characteristics in vitro (Kishimoto et al, 2000;Shimizu and Morgan, 2004;Rendl et al, 2008), DPAC could be more potentiated by the addition of activators of other signaling pathways, including the Sonic hedgehog, Notch, and Endothelin pathways (Gao et al, 2008;Driskell et al, 2009;Hu et al, 2010). In contrast to DP cells, fibroblasts cultured in DPAC reduced ALP expression (data not shown).…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, a recent report showed that laminin ␣5 in the hair follicle basement membrane is important for cilia structure and function. 31 However, here a direct effect of laminin ␣5 reduction on tubular epithelial cell behavior seems not to be the complete story; neither mode of glomerular rescue should affect the TBMs, yet cystogenesis was inhibited. There are no precedents for congenital nephrotic syndrome and/or hematuria causing early cystogenesis in humans or in mice.…”
Section: Discussionmentioning
confidence: 99%
“…We identify a distinctive distribution of Lam1 that is associated with sites of cilia formation during KV morphogenesis. Interestingly, in mammals, Lam-511 regulates primary cilia formation during dermal papilla development (Gao et al, 2008), suggesting that the role of laminin in ciliogenesis may be conserved in different organs and across species. Yet the mechanism by which Lamb1a modulates cilia formation is not clear.…”
Section: Research Article Laminin and Organ Lateralitymentioning
confidence: 99%